Anti-Inflammatory and Anti-Oxidant Effect of Dimethyl Fumarate in Cystic Fibrosis Bronchial Epithelial Cells - Onofrio Laselva (Cells, 2021)
Cystic Fibrosis (CF) is caused by mutations on the CF transmembrane conductance regulator (CFTR) gene and is associated with chronic infection and inflammation. Recently, it has been demonstrated that LPS-induced CFTR dysfunction in airway epithelial cells is due to an early oxidative stress. Dimethyl fumarate (DMF) is an approved anti-inflammatory and anti-oxidant drug for auto-immune and inflammatory diseases, but its role in the CF has never been investigated. In this study, we examined the effect of DMF on CF-related cytokines expression, ROS measurements and CFTR channel function. We found that DMF reduced the inflammatory response to LPS stimulation in both CF and non-CF bronchial epithelial cells, both as co-treatment and therapy, and restored LPS-mediated decrease of Trikafta™-mediated CFTR function in CF cells bearing the most common mutation, c.1521_1523delCTT (F508del). DMF also inhibited the inflammatory response induced by IL-1β/H2O2 and IL-1β/TNFα, mimicking the inflammatory status of CF patients. Finally, we also demonstrated that DMF exhibited an anti-oxidant effect on CF cells after different inflammatory stimulations. Since DMF is an approved drug, it could be further investigated as a novel anti-inflammatory molecule to ameliorate lung inflammation in CF and improve the CFTR modulators efficacy.